The creative process of two Indonesian NFT artists from the perspective of actor-network theory - Bastari, Rendy Pandita; Resmadi, Idhar; Lukito, Wahyu (citeus, 2023)
The development of crypto has resulted in NFT (non-fungible token) derivation. Artists began to explore the NFT market with its potential. NFT artists have different ways to get engagement and establish themselves in the world of NFT, whether in terms of artwork substance or in the social field. This study aims to deconstruct the actors behind NFT artists to elucidate the visual style and the social engagement of artists in the world of NFT. The method used in this study is a qualitative approach with data validation from interviews and NFT artwork samples. The data was subsequently processed using actor-network theory (ANT) to analyze and trace the actors behind the NFT artists. Two Indonesian artists, namely Angga Tantama and Mufti Prianka, became the study cases in this research. The result of this study shows heterogeneous actors who support the artists in their work's substance and social engagement. In the case of Mufti Prianka, NFTs influenced him to explore the possibilities of creating digital artworks, whereas for Angga, NFT platforms became one of his well-established channels to publish artworks. Based on their networks, the two Indonesian artists studied have different approaches and motivations in creating and engaging with NFTs.